Quality management and cost of education at private universities in Bangladesh: An evaluation - A. Ashraf, Mohammad (2007)
An exploratory survey was conducted to analyze the consumers’ evaluation of private higher education sectors in Bangladesh with particular reference to the quality as well as the cost of education. The sample was taken on a random basis from about ten private universities in Dhaka metropolitan area. The respondents (students) were asked to evaluate the quality and the cost of education at private universities in Bangladesh. Respondents ranked the attributes on a number of itemized seven-point scale ratings bounded at each end by one of two bipolar adjectives. The result of this study shows that faculty credentials, academic calendar, campus facility, research facility and cost of education are associated with quality education and that the consumers feel most of the private universities in Bangladesh provide quality education at reasonable costs.